Economy-Wide Estimates of the Implications of Climate Change: A Joint Analysis for Sea Level Rise and Tourism - Francesco Bosello; Andrea Bigano; Roberto Roson; Richard S.J. Tol (Fondazione Eni Enrico Mattei (FEEM), 2006)
Climate change impacts on human life have well defined and different origins, nevertheless in the determination of their final effects, especially those involving social-economic responses, interactions among impacts are likely to play an important role. This paper is one of the first attempts to disentangle and highlight the role of these interactions. It focuses on the economic assessment of two specific climate change impacts: sea-level rise and changes in tourism flows. By using a CGE model the two impacts categories are first analyzed separately and then jointly. Comparing the results it is shown that, even though qualitatively joint effects follow the outcomes of the disjoint exercises, quantitatively impact interactions do play a significant role. Moreover it has been also possible to disentangle the relative contribution of each single impact category to the final result. In the case under scrutiny demand shocks induced by changes in tourism flows outweigh the supply side shock induced by the loss of coastal land.
Keywords: C68; D58; Q25; 330; Climate Change; Sea Level Rise; Tourism; Computable General Equilibrium Models; Klimaveränderung; Überschwemmung; Tourismus; Allgemeines Gleichgewicht; Welt